Goat systems of Villuercas-Ibores area in SW Spain: Problems and perspectives of traditional farming systems - Gaspar, P.; Escribano, A. J.; Mesías, F. J.; Escribano, M.; Pulido, A. F. (Small Ruminant Research, 2011)
A study of dairy goat systems was carried out in the “Villuercas-Ibores” region, a mountainous area located in the south-west of the Iberian Peninsula (Cáceres, Spain). This territory is characterized by difﬁcult orography and a fairly harsh climate, and has low indices of income and population density. Goat production in the area has contributed notably to its economic and social development historically, but there has been a marked recession in goat-based activities in recent decades, leading to changes in the type and intensity of land use. The purpose of the study is to analyze the main characteristics of the current goat farming systems in a zone in which goat milk production is possible under a Protected Designation of Origin (PDO) brand “Ibores Cheese”, and to establish a farm classiﬁcation that will allow groups of holdings with common characteristics to be identiﬁed, so that they can be compared and their performance evaluated. The data were obtained through direct interviews to goat farmers (n = 61) within the geographical area of the PDO “Ibores Cheese”. Speciﬁc information on management was collected, together with data on family characteristics, labour, livestock numbers, land use, installations, continuity, recent changes in farming, and the farmer’s opinions. A principal component analysis (PCA) was used to examine the relationships among the quantitative variables, then a two-step cluster analysis was applied using the factors obtained in the PCA and categorical variables. This resulted in a farm typology of three groups distinguished by their land use, goat breed, and PDO membership. The best management practices and productivity results were obtained by the farms furthest removed from the traditional systems. The ﬁrst group of farms is characterized by small size ﬂocks. Many of these farms do not belong to the PDO and therefore they have chosen breeds that are not allowed by the PDO regulations. Most of them are semi-intensive or intensive farms. The second group consist of extensive farms with large size ﬂocks of goats complemented with sheep farming and, occasionally, with beef cattle or Iberian pig. They have got technically suitable milking rooms, although the availability of other infrastructure is poor. Finally, the third group identiﬁed includes extensive farms whose goat ﬂock size is very similar to that of group 1, but in 70% of the cases they are mixed farms, mainly combining goat with sheep ﬂocks. Most of them are producing milk that is sold to ﬁrms producing PDO cheese. It is the group closest to the traditional farming system and the farms have small ﬂocks of low productivity per goat, raising autochthonous breeds and their crossbreeds.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Farm typology; goat systems; Management practices; multivariate analysis; PDO “Ibores Cheese”

Phytostructural characterization of several vegetation types in northern Portugal. II. The structural expressivity and the resistance of the vegetation - Crespí, A; Bernardos, S; Castro, A; Fernandes, C P; Amich, F (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract The encouraging results obtained in a previous work induced the authors to pursue here the characterization of the structure of the vegetation in northern Portugal, using the phytostructural methodology proposed earlier by the authors. With this objective, eight different types of vegetal communities, representative of the apparent states of the successional process present in this area, and representing the diversity of plant community types in the same area, were selected. The phytostructural method was elaborated on the basis of three types of structural basic matrices regarding diversity, abundance and cover. The data obtained were collected in a contingency matrix, which was then treated by means of a statistical multivariate analysis. Three structural tendencies emerged from this analysis. With the aim of studying their stability, the results are discussed in terms of resistance and resilience, according to the Highest Expressive Amplitude (HEA) concept, and by considering the intra- and inter-community structural dynamics as structural parameters. The data obtained suggest structural situations with different degrees of non-equilibrium that reflect resistance to environmental factors. The resistance of the vegetation is correlated with the apparent functional connectivity detected for the communities analysed.
doi: 10.1080/11263500500333651
Keywords: Expressive capacity; multivariate analysis; Portugal; structural stability

Phytostructural characterization of several vegetation types in northern Portugal. II. The structural expressivity and the resistance of the vegetation - Crespí, A.; Bernardos, S.; Castro, A.; Fernandes, C. P.; Amich, F. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract The encouraging results obtained in a previous work induced the authors to pursue here the characterization of the structure of the vegetation in northern Portugal, using the phytostructural methodology proposed earlier by the authors. With this objective, eight different types of vegetal communities, representative of the apparent states of the successional process present in this area, and representing the diversity of plant community types in the same area, were selected. The phytostructural method was elaborated on the basis of three types of structural basic matrices regarding diversity, abundance and cover. The data obtained were collected in a contingency matrix, which was then treated by means of a statistical multivariate analysis. Three structural tendencies emerged from this analysis. With the aim of studying their stability, the results are discussed in terms of resistance and resilience, according to the Highest Expressive Amplitude (HEA) concept, and by considering the intra- and inter-community structural dynamics as structural parameters. The data obtained suggest structural situations with different degrees of non-equilibrium that reflect resistance to environmental factors. The resistance of the vegetation is correlated with the apparent functional connectivity detected for the communities analysed.
doi: 10.1080/11263500500333651doi: 10.1080/11263500500333651The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Expressive capacity; multivariate analysis; Portugal; structural stability

The use of climatic parameters and indices in vegetation distribution. A case study in the Spanish Sistema Central. - Gavilán, Rosario G. (International journal of biometeorology, 2005)
In this study, over 100 phytoclimatic indices and other climatic parameters were calculated using the climatic data from 260 meteorological stations in a Mediterranean territory located in the centre of the Iberian Peninsula. The nature of these indices was very different; some of them expressed general climatic features (e.g. continentality), while others were formulated for different Mediterranean territories and included particular limits of those indices that expressed differences in vegetation distribution. We wanted to know whether all of these indices were able to explain changes in vegetation on a spatial scale, and whether their boundaries worked similarly to the original territory. As they were so numerous, we investigated whether any of them were redundant. To relate vegetation to climate parameters we preferred to use its hierarchical nature, in discrete units (characterized by one or more dominant or co-dominant species), although it is known to vary continuously. These units give clearer results in this kind of phytoclimatic study. We have therefore used the main communities that represent natural potential vegetation. Multivariate and estimative analyses were used as statistical methods. The classification showed different levels of correlation among climatic parameters, but all of them were over 0.5. One hundred and eleven parameters were grouped into five larger groups: temperature (T), annual pluviothermic indices (PTY), summer pluviothermic indices (SPT), winter potential evapotranspiration (WPET) and thermal continentality indices (K). The remaining parameters showed low correlations with these five groups; some of them revealed obvious spatial changes in vegetation, such as summer hydric parameters that were zero in most vegetation types but not in high mountain vegetation. Others showed no clear results. For example, the Kerner index, an index of thermal continentality, showed lower values than expected for certain particular types of vegetation. Parameters relating to the water balance turned out to be very discriminative for separating vegetation types according to the season or the month when water begins to be scarce. Thus, water availability in soils is a limiting factor for the development of vegetation in spring or autumn as well as in summer. As expected, precipitation and temperature discriminated the altitudinal levels of vegetation. Finally, these index limits only worked in the territories where they were formulated, or in nearby areas.
The following values have no corresponding Zotero field: accession-num: 15997399
Keywords: climate; climatic indices; Mediterranean vegetation; multivariate analysis; phytoclimatology; Plants; Plants: classification; Principal component analysis; Seasons; Spain; Vegetation distribution; Weather

The use of climatic parameters and indices in vegetation distribution. A case study in the Spanish Sistema Central. - Gavilán, Rosario G (International journal of biometeorology, 2005)
In this study, over 100 phytoclimatic indices and other climatic parameters were calculated using the climatic data from 260 meteorological stations in a Mediterranean territory located in the centre of the Iberian Peninsula. The nature of these indices was very different; some of them expressed general climatic features (e.g. continentality), while others were formulated for different Mediterranean territories and included particular limits of those indices that expressed differences in vegetation distribution. We wanted to know whether all of these indices were able to explain changes in vegetation on a spatial scale, and whether their boundaries worked similarly to the original territory. As they were so numerous, we investigated whether any of them were redundant. To relate vegetation to climate parameters we preferred to use its hierarchical nature, in discrete units (characterized by one or more dominant or co-dominant species), although it is known to vary continuously. These units give clearer results in this kind of phytoclimatic study. We have therefore used the main communities that represent natural potential vegetation. Multivariate and estimative analyses were used as statistical methods. The classification showed different levels of correlation among climatic parameters, but all of them were over 0.5. One hundred and eleven parameters were grouped into five larger groups: temperature (T), annual pluviothermic indices (PTY), summer pluviothermic indices (SPT), winter potential evapotranspiration (WPET) and thermal continentality indices (K). The remaining parameters showed low correlations with these five groups; some of them revealed obvious spatial changes in vegetation, such as summer hydric parameters that were zero in most vegetation types but not in high mountain vegetation. Others showed no clear results. For example, the Kerner index, an index of thermal continentality, showed lower values than expected for certain particular types of vegetation. Parameters relating to the water balance turned out to be very discriminative for separating vegetation types according to the season or the month when water begins to be scarce. Thus, water availability in soils is a limiting factor for the development of vegetation in spring or autumn as well as in summer. As expected, precipitation and temperature discriminated the altitudinal levels of vegetation. Finally, these index limits only worked in the territories where they were formulated, or in nearby areas.
Keywords: climate; climatic indices; Mediterranean vegetation; multivariate analysis; phytoclimatology; Plants; Plants: classification; Principal component analysis; Seasons; Spain; Vegetation distribution; Weather